2024
DOI: 10.1108/meq-08-2023-0274
|View full text |Cite
|
Sign up to set email alerts
|

Electricity energy-saving behavior of households in Jordan: a qualitative study

Safaa Alwedyan

Abstract: PurposeGiven the rapid increase in energy consumption in the residential sector in Jordan recently, the question of how to promote energy-saving behavior in Jordanian households is an emerging topic that is receiving increasing attention from scholars and academics. Generally, there is an unresolved paradox in the literature concerning electricity-saving behaviors. On one hand, numerous studies highlight energy-saving behaviors. On the other hand, recent research indicates the presence of significant untapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…A literature review revealed that previous studies investigating resident behavior employed questionnaires with different types of questions depending on the project's scope and elements under investigation [24,40,42]. A total of 250 distinct questions were gathered from previous surveys, with redundant questions yielding similar responses being removed.…”
Section: Survey Design and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review revealed that previous studies investigating resident behavior employed questionnaires with different types of questions depending on the project's scope and elements under investigation [24,40,42]. A total of 250 distinct questions were gathered from previous surveys, with redundant questions yielding similar responses being removed.…”
Section: Survey Design and Analysismentioning
confidence: 99%
“…These issues have gained significance in the context of the pandemic and the growing research on using IoT sensor grids for occupancy behavior and IAQ monitoring [21,22]. This insight into the importance of occupant behavior sets the stage for examining specific elements of building design that can either mitigate or exacerbate these challenges [23,24].…”
Section: Introductionmentioning
confidence: 99%